Estudio de factibilidad para la creación de una empresa productora de camisas de dotación con telas ecológicas (2021)
This article will present feasibility study for creating a company producing work uniforms and apparel with Green textiles. We will show market, technical, administrative, and financial analyses to confirm the feasibility of creating a company with this type of fabric and, therefore, contribute to reducing the environmental footprint left by the textile industry.